Hepatoblastoma in Explanted Livers of Patients With Biliary Atresia. Issue 2 (August 2016) - Amir, Achiya Z.; Sharma, Ajay; Cutz, Ernest; Avitzur, Yaron; Shaikh, Furqan; Kamath, Binita M.; Ling, Simon C.; Ghanekar, Anand; Ng, Vicky L.
ABSTRACT: Objectives: Surveillance of hepatic nodules for malignant transformation to hepatocellular carcinoma is important in the monitoring of patients with biliary atresia (BA). To date, only 2 published case reports describe the finding of hepatoblastoma (HB) in this setting. The present study aimed to investigate this association of HB and BA, and to assess the utility of alpha-fetoprotein (aFP) as a marker in the diagnosis. Methods: A retrospective study of all patients who underwent isolated liver transplantation (LTx) for the primary diagnosis of BA at a single center, between January 1999 and June 2014, was conducted. Patient demographics, pre-LTx aFP levels, and histologic examination of native liver explants were reviewed. Results: One hundred two (44% men, median age 11 months) patients underwent LTx for BA. Two (2%) explants examinations were confirmatory for concomitant HB; both patients had abnormally elevated aFP. Overall, 56 (55%) patients had available pre-LTx aFP levels. Recipients with persistently abnormal aFP levels (n = 20, 36%) were older at hepatoportoenterostomy (107 vs 68 days, P = 0.02) and younger at LTx surgery (359 vs 1713 days, P < 0.01), compared to patients with constantly normal levels (n = 24, 43%). Conclusions: In our cohort, HB was found to coexist in approximately 2% of patients with BA undergoing LTx, far exceeding the hypothetical anticipated incidence of 1:10 billion for the concomitant diagnoses. Elevated serum aFP levels may be sensitive but not specific for HB in this context. Further research is required to identify specific mechanisms and risk factors.